Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1464-410x.2008.07461.x
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA expression of monocyte chemoattractant protein‐1 and interleukin‐6 in stone‐containing kidneys

Abstract: OBJECTIVESTo investigate the intrarenal mRNA expression of monocyte chemoattractant protein‐1 (MCP‐1) and interleukin‐6 (IL‐6) in patients with nephrolithiasis, and to evaluate whether their expression is associated with renal function, as oxidative stress and inflammation are involved in the pathogenesis of nephrolithiasis.PATIENTS, SUBJECTS AND METHODSRenal biopsies from near the stone, and blood and 24‐h urine specimens were collected from 29 patients with nephrolithiasis. Control renal tissues were taken f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…We also show an increased expression of 8-OHdG lesion in stone-containing renal tissues [182]. MCP-1 and IL-6 mRNA expression in stone-containing kidney tissues are increased, and their increment is related to declined creatinine clearance [183]. Our findings indicate that patients with nephrolithiasis persistently have increased oxidative stress and intrarenal inflammation, and these pathological changes contribute to renal impairment.…”
Section: Oxidative Stress In Urolithiasissupporting
confidence: 53%
“…We also show an increased expression of 8-OHdG lesion in stone-containing renal tissues [182]. MCP-1 and IL-6 mRNA expression in stone-containing kidney tissues are increased, and their increment is related to declined creatinine clearance [183]. Our findings indicate that patients with nephrolithiasis persistently have increased oxidative stress and intrarenal inflammation, and these pathological changes contribute to renal impairment.…”
Section: Oxidative Stress In Urolithiasissupporting
confidence: 53%
“…Previous studies have hypothesized that renal cell injury and inflammation are related to the development of renal stones and demonstrated an increase in IL-6 in patients with urolithiasis [25][26][27]. Boonla et al, also showed increased mRNA expression of IL-6 and monocyte chemoattractant protein -1 in tissue from renal biopsy from kidneys containing calculi [28].…”
Section: Discussionmentioning
confidence: 81%
“…IL-6 has been previously demonstrated to enhance osteoclastogenesis by the induction of the NF-κB ligand in osteoblastic cells (66) and has also shown to be the central pathogenic player in arthritis. Given the multifacted role of IL-6, our findings therefore suggest that the increased production of IL-6 under basal conditions in the kidney may explain the development of both hypercalciuria and nephrolithiasis in Clcn5 KO mice, although a direct correlation has not been established (67, 68). Moreover, elevated IL-6 is involved in defective bone mineralization, which may also explain the sporadic presentation of rickets/osteomalacia in patients with Dent disease (27, 51, 69–71).…”
Section: Discussionmentioning
confidence: 83%